Terpene exposure and respiratory effects among workers in Swedish joinery shops - Eriksson, KA; Levin, Jo; Sandström, T; Lindström-Espeling, K; Lindén, Gerd; Stjernberg, NL (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'Exposure to monoterpenes (I-pinene, J-pinene and q3-carene) in joinery shops was studied in Sweden during the processing of Scot's pin and the acute respiratory effects among the employees were evaluated. Methods A cross-sectional study of 38 workers was carried out in 4 joinery shops. The investigation included personal air sampling of monoterpenes, biological monitoring of metabolites of I-pinene in the workers' urine, interviews following a standardized questionnaire, and dynamic spirometry. Results The personal exposure to monoterpenes in the joinery shops was 10--214 mg/m3. The correlation (correlation coefficient = 0.69) between exposure to I-pinene and verbenols (metabolites from I-pinene) in urine was relatively good. No acute effects on forced vital capacity or forced expiratory volume during 1 s were detected. The workers had significantly reduced preshift lung function values when compared with the values of a local reference group, even when smokers and ex-smokers were excluded. Conclusions Personal exposure to the monoterpenes I-pinene, J-pinene, and q3-carene in joinery shops may exceed the present Swedish occupational exposure limit of 150 mg/m3 during the winter season when workroom air is commonly recirculated. The determination of metabolites of I-pinene (verbenols) in urine can be used as an index of exposure to fumes released during wood-treating processes. The results from the lung function tests indicate chronic rather than acute reactions in the airways. The fact that there were no major changes in lung function over a workshift indicates chronic reaction in the airways.
Keywords: lung function; metabolite; monoterpene